City beasts : fourteen stories of uninvited wildlife - Kurlansky, Mark (Riverhead Books, 2015)
In these stories, Mark Kurlansky journeys to his familiar haunts like New York's Central Park or Miami's Little Havana but with an original, earthy, and adventurous perspective. From baseball players in the Dominican Republic to Basque separatists in Spain to a restaurant owner in Cuba, from urban coyotes to a murder of crows, Kurlansky travels the worlds of animals and their human counterparts, revealing moving and hilarious truths about our connected existence. In the end, he illuminates how closely our worlds are aligned, how humans really are beasts, susceptible to their basest instincts, their wildest dreams, and their artful survival.